Fe−N3/C Active Catalytic Sites for the Oxygen Reduction Reaction Prepared with Molecular‐Level Geometry Control through the Covalent Immobilization of an Iron−Terpyridine Motif onto Carbon. Issue 5 (24th January 2019) - Fruehwald, Holly M.; Ebralidze, Iraklii I.; Zenkina, Olena V.; Easton, E. Bradley
Abstract: A model for a non‐precious metal catalyst for the oxygen reduction reaction (ORR) in aqueous media has been prepared by functionalizing a commercial Vulcan XC‐72 carbon support with a terpyridine‐based nitrogenous ligand. The terpyridine ligand geometry allows the formation of active catalytic sites by selectively embedding a N3 /C structural motif into the carbon support confirmed by using thermogravimetric analysis (TGA) and X‐ray photoelectron spectroscopy (XPS) measurements. Room‐temperature metal–ligand coordination results in the desired Fe−N3 /C moieties on the surface. This model system was used to demonstrate the catalytic activity of the surfaces containing mainly Fe−N3 sites for the ORR in acidic and basic media. Importantly, we demonstrate that the system could be prepared under mild reaction conditions, does not require high‐ temperature treatments, and shows catalytic activity for the ORR. Interestingly, when the system was pyrolyzed in an N2 atmosphere at 700 °C the resulting activity declined. The non‐heat‐treated Fe−N3 /C surface demonstrates comparable activity in acidic electrolyte medium when compared to most literature catalysts that are typically heat treated to produce four nitrogen atoms coordinated to one iron center (Fe−N2+2 /C). Interestingly, despite the fact that many systems reported so far in the literature exhibit enhanced activity after heat treatment, our system showed an increase in activity when the material was not pyrolyzed. Abstract : Is a Fe−N3 /C site active towards ORR ? This active site for non‐precious metal catalysis was never before proposed. Experiments demonstrate that a Fe−N3 /C design shows activity for the oxygen reduction reaction (ORR) in both acidic and basic media. The material is shown to perform well without the need for further heat treatment. Using a surface modification approach, a surface can be produced with mostly pyridinic nitrogens, which are believed to be highly active for the ORR.